1997
DOI: 10.1136/gut.41.3.333
|View full text |Cite
|
Sign up to set email alerts
|

Red kidney bean lectin is a potent cholecystokinin releasing stimulus in the rat inducing pancreatic growth

Abstract: Background-Lectins are proteins capable of specific binding to carbohydrates without altering their covalent structure. As an essential part of plants they are ingested in our daily diet. By binding to glycosyl side chains of receptors lectins can mimic or inhibit the action of the ligand. Oral administration of phytohaemagglutinin (PHA) in rats dose dependently induces growth of the small intestine and the pancreas by an unknown mechanism. Aims-To investigate the mechanism of PHA induced intestinal and pancre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 46 publications
5
52
1
Order By: Relevance
“…According to Liener (1994) and Rådberg et al (2001) lectins can modulate hormone secretion (insulin, CCK, gastrin). At high doses, lectin intake can lead to intestinal and pancreatic overgrowth (Jordinson et al, 1996;Herzig et al, 1997;Grant et al, 2000;Kelsall et al, 2002). Our results showed that the applied doses of PSA and SBA did not result in significant pancreatic overgrowth, which is in agreement with Li et al (2003a,b) and our previous study (Czerwiński et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…According to Liener (1994) and Rådberg et al (2001) lectins can modulate hormone secretion (insulin, CCK, gastrin). At high doses, lectin intake can lead to intestinal and pancreatic overgrowth (Jordinson et al, 1996;Herzig et al, 1997;Grant et al, 2000;Kelsall et al, 2002). Our results showed that the applied doses of PSA and SBA did not result in significant pancreatic overgrowth, which is in agreement with Li et al (2003a,b) and our previous study (Czerwiński et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…Many authors have shown that lectins interacting with brush border membrane can modulate CCK secretion by intestinal endocrine cells (Jordinson et al, 1996;Herzig et al, 1997;Li et al, 2003a,b). Moreover, absorbed lectins can immediately interact with pancreatic cells Kelsall et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCK is released from enteroendocrine I-cells in the mucosa of duodenum and proximal jejunum in the intestinal phase of digestion in response to fatty acids and proteins in the intestinal lumen [25] and other duodenal peptides [26]. CCK activates the CCK1 receptors in the afferent fibers of the vagus nerve which in addition to the elevated plasma CCK levels mediates the digestive effects of CCK by stimulating exocrine pancreatic secretion and gallbladder contraction.…”
Section: Discussionmentioning
confidence: 99%
“…The higher levels of glucose in the blood of piglets receiving kidney bean lectin extract in our study may be a sign of high reactivity of the exocrine pancreas in these animals as compared with the control group. These binding results in the stimulation of the release of cholecystokinin and glucagon-like peptides (Herzig et al, 1997;Rådberg et al, 2001), two hormones known to stimulate exo-and endocrine pancreas function. According to Grant et al (1987), a high lectin content induces glycogen catabolism and as a result of this process, serum glucose levels increase.…”
Section: Discussionmentioning
confidence: 99%